Mono-Unit Alar Rim Graft Technique for Tip-Alar Margin Support. (5th June 2020) - Kim, Shin Ae; Jang, Yong Ju
Abstract: Background: The appropriate treatment of alar rim deformities, such as alar pinching or concavity, and soft triangle notching is essential for perfecting nasal aesthetics. Objectives: The authors introduced the "mono-unit alar rim graft" technique as a treatment option for these abnormalities. Methods: A case series of 29 rhinoplasties conducted by the senior author between May 2017 and June 2019 utilizing the mono-unit alar rim graft technique was retrospectively reviewed. The surgical technique involved an open approach with costal cartilage harvesting. The cortical portion of the harvested costal cartilage was sectioned into a 1-mm-thick strip and soaked with saline for about 15 minutes to let the natural warping occur. The curved cartilage graft was then trimmed, and the midportion was sutured to the tip in an onlay fashion. Both ends of the graft were housed in the vestibular pocket. Patient demographic data and pre- and postoperative facial photos were reviewed. Results: Among the 29 cases analyzed, 14 (48.3%) were men and 15 (51.7%) were women. Ten (34.5%) patients had a preoperative parenthesis deformity, but a near-complete correction was achieved in 8 (80.0%) cases. An alar concavity from the basal view was found in 16 patients, 15 (93.8%) of whom had a partial or near-complete correction. Eleven patients had soft triangle notching, 9 (81.8%) of whom had a partial or near-complete correction. There were no technique-related complications in this patient series. Conclusions: The mono-unit alar rim graft technique is a viable option for treating various alar rim deformities. Level of Evidence: 4: